(untitled) (Journal of Economic Research & Business Administration, 2015)
Need of regional integration locates in article for the countries of Central Asia and considering the economic capacity of the region, its main strategic directions are allocated. And still, the factors interfering development of integration processes among the countries of Central Asia are analyzed and solutions of these problems are offered. The modern geopolitical situation in the Central Asian region is influenced by a number of tendencies of the global character, capable to make a certain impact on regional economical and political security in medium-term prospect. For the countries of Central Asia the current decade has to become decisive – or they will manage to find the general way of integration to world economic system with sovereignty preservation, or remain as raw appendages of the developed countries. Creation of competitive economy, ensuring stability in the region, increase of welfare of the people has to become a result of development of mutually beneficial regional cooperation of Central Asia. Only uniform Central Asia can give the worthy answer to threats and calls of globalization and to receive a worthy place in the world scene.